The expression of the soluble HFE corresponding transcript is up-regulated by intracellular iron and inhibits iron absorption in a duodenal cell model - Silva, Bruno (2014)
Background and aims: Dietary iron absorption regulation is a key-step for the maintenance of body iron homeostasis. Besides the HFE full-length protein, the HFE gene codes for alternative splicing variants responsible for the synthesis of a soluble form of HFE protein (sHFE). Here we aimed to determine whether sHFE transcript levels respond to different iron conditions in duodenal, macrophage and hepatic cell models, as well, in vivo, in the liver. Furthermore, we determined the functional effect of the sHFE protein on the expression of iron metabolism-related genes in a duodenal cell model. Methods: The levels of sHFE transcripts were measured in HuTu-80, activated THP1 and HepG2 cells, after holo-Tf stimulus, as well as in RNA from liver biopsies of chronic HCV patients. Moreover, the expression of iron metabolism-related genes was determined by RT-qPCR after the overexpression of sHFE protein. Results: Our results showed that the sHFE corresponding transcripts expression is up-regulated by intracellular iron, despite the total HFE levels not being affected. Peripheral blood iron biomarkers do not correlate with sHFE levels at the liver of HCV patients. Hephaestin and duodenal cytochrome b expressions are down-regulated by both endogenous full-length HFE and sHFE proteins. Exogenous sHFE stimulus also down-regulates hephaestin levels by an endocytosis dependent mechanism. Conclusions: sHFE is an important iron metabolism homeostasis regulator which levels vary accordingly to intracellular iron. It controls both hephaestin and duodenal cytochrome b expressions and consequently dietary iron absorption by the duodenum.